2008
DOI: 10.1590/s1807-03022008000100001
|View full text |Cite
|
Sign up to set email alerts
|

On hydromagnetic rotating flow of a dusty fluid near a pulsating plate

Abstract: Abstract. An initial value problem is solved for the motion of an incompressible viscous conducting fluid with embedded small inert spherical particles bounded by an infinite rigid nonconducting plate. Both the plate and the fluid are in a state of solid-body rotation with constant angular velocity about an axis normal to the plate. The unsteady flow is generated in the fluidparticle system due to velocity tooth pulses subjected on the plate in presence of a transverse magnetic field. It is assumed that no ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Ghosh and Ghosh [6] solved the same problem as that of authors [5] replacing the boundary condition at the upper plate of the channel by rectified sine pulses instead of tooth pulses as encountered by authors [5]. In a subsequent paper Ghosh and Ghosh [7] also examined the hydromagnetic flow of a two-phase fluid near a pulsating plate with a view to its application in the analysis of suspension boundary layers. On the other hand, Datta & Datta [8] [9] discussed the heat transfer to pulsatile flow of a dusty fluid in pipes and channels with a view to their application in the analysis of blood flow.…”
Section: Introductionmentioning
confidence: 93%
“…Ghosh and Ghosh [6] solved the same problem as that of authors [5] replacing the boundary condition at the upper plate of the channel by rectified sine pulses instead of tooth pulses as encountered by authors [5]. In a subsequent paper Ghosh and Ghosh [7] also examined the hydromagnetic flow of a two-phase fluid near a pulsating plate with a view to its application in the analysis of suspension boundary layers. On the other hand, Datta & Datta [8] [9] discussed the heat transfer to pulsatile flow of a dusty fluid in pipes and channels with a view to their application in the analysis of blood flow.…”
Section: Introductionmentioning
confidence: 93%
“…Soo [4], established the fundamental theory of multi-phase flows. The contribution of Michael and Miller [5], Healy [6], Vimala [7], Gupta and Gupta [8], Venkateshappa et al [9], Venkatesh and Kumara [10], Ghosh and Sana [11], Gosh and Gosh [12], Gireesha et al [13], Gosh and Debnath [14], to the literature can be found during the same decade.…”
Section: Introductionmentioning
confidence: 99%
“…Further, Ghosh and Sana [9] also carried out the investigation of the transversely applied magnetic field to the fluid having dust particles of spherical shape. In another paper, Gosh and Gosh [10] shared their efforts about dusty fluid by finding that in presence of pulsation when the concentration of the dust particles is increased, it increases the velocity of the dusty fluid near the plate in the case when time is large while rotation is small. The study of the two-dimensional flow of dusty fluid over a stretching sheet in the presence of radiation is carried out by Gireesha et al [11], for the analysis of this phenomenon they have transformed the highly non-linear momentum and heat equation into coupled ordinary differential equations by similarity transformation.…”
Section: Introductionmentioning
confidence: 99%